MENDISTRIBUSIKAN VIRTUAL LAN DENGAN WIRELESS VIRTUAL ACCESS POINT MENGGUNAKAN METODE NDLC - Sabar Hanadwiputra; Marisa (POLITEKNIK PIKSI GANESHA, 2019)
With the development of information technology and computers at this time. With ease, we can get the various information that we want and without realizing it has pushed the number of computer and internet users to be even greater. Thus, the increasing number of users or users who use the internet network or hostpot needs to have a grouping or division of internet networks. so that the network used does not accumulate in one network location which will cause the internet network to become weak. however, it is specified or divided into several internet network locations so that the usage is regular and running well. Therefore, in distributing us using VLAN (Virtual Local Area Network) is a technology that allows a LAN (Lan Area Network) to be divided into several different stages. Vlan also allows merging separate physical locations, but is in the same stage. VLAN (Virtual Local Area Network) which functions as a flexible and regular distribution of networks.